Hubungan Tingkat Pemahaman Hak Asasi Manusia Dengan Sikap Anti Diskriminasi Mahasiswa PPKN FKIP Universitas Lampung - Putri Agustina Cahaya Negara; Berchah Pitoewas; Rohman .; Yunisca Nurmalisa; Karyadi Hidayat (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to determine the relationship between the level of understanding of Human Rights (HAM) and anti-discrimination attitudes of students in the Pancasila and Citizenship Education (PPKn) Study Program, Faculty of Teacher Training and Education, University of Lampung. This study used a quantitative method with a correlational approach. The research sample consisted of 76 students from the classes of 2022, 2023, and 2024. Data collection techniques used a test to measure human rights understanding and a questionnaire to measure anti-discrimination attitudes. Data analysis was carried out using a correlation test. The results of the study indicate a significant relationship between the level of human rights understanding and students' anti-discrimination attitudes. This indicates that the higher the students' human rights understanding, the higher their anti-discrimination attitudes. Thus, human rights understanding is an important foundation in forming inclusive and equitable social attitudes in the academic environment.